Factors Associated with Cigarette Smoking and Motivation to Quit among Street Food Sellers in Vietnam - Xuan Thanh Thi Le (International Journal of Environmental Research and Public Health, 2018)
Since 2013, smoke-free signs in public places, including in restaurants and food stores, have been introduced in Vietnam, aiming to prevent passive smoking. Although extensive research has been carried out on second-hand smoking among clients in public places (e.g., hospitals, restaurants) in Vietnam, no single study exists which captures the current practice of smoking among street food outlets. This study aims to estimate the prevalence of smoking and identify factors associated with smoking status and cessation motivation amongst food sellers in Vietnam. A cross-sectional study involving 1733 food providers at outlets was conducted in 29 districts in Hanoi capital, Vietnam, in 2015. The prevalence of smoking amongst food sellers was determined to be 8.5% (25% for men and 0.8% for women). The enforcement of the smoke-free policy remains modest, since only 7.9% observed outlets complied with the law, providing a room designated for smokers. Although approximately 80% of the participants were aware of the indoor smoke-free regulations in public places, such as restaurants and food stores, 40.2% of smokers reported no intention of quitting smoking. A percentage of 37.6% of current smokers reported that despite having intentions to quit, they did not receive any form of support for smoking cessation. Being male and having hazardous drinking habits and a poor quality of life were all factors that were significantly associated with smoking status. Additionally, having awareness of smoking’s adverse effects and being frequently supervised by the authority were associated with a greater motivation to quit. This study highlights the importance of an accompanying education and smoking cessation program in addition to the frequent inspection and reinforcement of smoke-free policy in food stores. This research extends on our knowledge of smoking prevalence and its factors related to smoking events and motivation to quit among street food outlets. Overall, this study strengthens the idea that more government efforts towards preventing passive smoking and smoking cessation education are necessary in restaurants and other street food outlets.